Cybersecurity Mesh and Edge Computing on the Analytics Platform of the Indonesian Telecommunications Industry - Fika Ulfa Widowati (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2025)
This research analyzes the implementation of cybersecurity mesh and edge computing on analytics platforms in the Indonesian telecommunications industry. The geographical complexity and disparity of Indonesia's telecommunications infrastructure create unique challenges in securing and optimizing analytics platforms using a mixed-method approach with a sequential explanatory design. The research involves 15 national telecommunications operators representing 85% of the market share. Data were collected through structured surveys, in-depth interviews, and field observations during the period from January to June 2024. The research results show that the integration of cybersecurity mesh with edge computing increases operational efficiency by 45% and reduces latency by up to 75% compared to conventional architecture. The developed integration model successfully accommodates Indonesia's geographical characteristics and complies with national regulations. The implementation of a cybersecurity mesh increased the effectiveness of cyber threat detection by 89%, while edge computing optimization resulted in bandwidth savings of up to 60%. This research contributes to the development of a national blueprint for optimizing telecommunications analytics platforms that are adaptive to Indonesia's conditions. These findings provide practical implications for telecommunications operators in optimizing digital infrastructure. This can enrich the literature by considering integration models from geographical and regulatory aspects.